Pengaruh Subtitusi Rumput Lapangan Dengan Limbah Serai Wangi Terhadap Kandungan Bahan Kering, Bahan Organik, Dan Protein Kasar Sebagai Bahan Pakan Ternak Ruminansia - Fadjra, Nurul; Astuti, Tri; Akbar, Syahro Ali; Basyirun, Fajri; Sari, Rica Mega (Program Studi peternakan, 2023)
This research aims to determine the influence of substituting field grass with citronella waste in the ration on the content of dry matter, organic matter, and crude protein as ruminant feed ingredients. This study used a completely randomized design with 5 treatments and 3 replications. The treatments consisted of P0 (50% field grass + 0% citronella waste + 50% concentrate), P1 (40% field grass + 10% citronella waste + 50% concentrate), P2 (30% field grass + 20% citronella waste + 50% concentrate), P3 (20% field grass + 30% citronella waste + 50% concentrate), P4 (10% field grass + 40% citronella waste + 50% concentrate), and P5 (0% field grass + 50% citronella waste + 50% concentrate). The results showed that the treatments had different effects, which were not significant (P>0.05).